Developing a TPACK-based science module through project-based learning to enhance elementary students’ 4Cs skills - Saleha, Saleha; Nadar, Nadar; Masnur, Masnur (Jurnal Prima Edukasia, 2026)
Science education in elementary schools in Pinrang Regency is still dominated by conventional approaches. There is low integration of technology and limited development of 21st-century skills such as critical thinking, communication, collaboration, and creativity. This study aims to develop and implement a Science teaching module based on TPACK and integrated with the Project-Based Learning (PjBL) model. The goal is to enhance students' Four Cs skills. The research used a Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) within a Mixed Methods design. Data were collected through expert validation questionnaires (Aiken’s V coefficient), teacher and student practicality questionnaires, structured classroom observation protocols (17 indicators, inter-rater reliability = 0.87), and semi-structured interviews with 12 teachers and 12 school principals. Pre-test and post-test instruments measured Four Cs competencies. Quantitative data were analyzed using normalized gain (N-Gain) calculations and paired-samples t-tests (SPSS v. 28). Qualitative data underwent thematic analysis following Braun and Clarke’s (2006) six-phase framework in NVivo 12. The results showed that the developed module had high validity and practicality. It achieved average validity and practicality scores of 90%. The module effectively improved students' Four Cs skills, with an average N-Gain score ranging from 0.49 in the limited trial to 0.51 in the wide-scale trial. This study contributes to the development of a teaching model that integrates technology and project-based methods to improve 21st-century skills in elementary education, especially in regions with limited infrastructure. The findings also suggest that improving teacher training and providing adequate infrastructure support are essential for the sustainability of the model's implementation.